Field survey of air conditioner temperature settings in a hot, dry climate (Oman) - Abdul Majid, Noor Hanita; Takagi, Nozomi; Hokoi, Shuichi; Ekasiswi, Sri Nastiti; Uno, Tomoko (Taylor & Francis Group, 2014)
In conventional air-conditioning design, the comfortable range of temperatures is between 25◦C and 27◦C with relative humidity levels of 40% to 60%; these numbers vary only slightly based on a person’s race and country. Several studies in tropical climates show that the observed thermal comfort requirement often does not agree with those obtained based on experiments, which have mainly used North American subjects. However, there is no consistent rationale that explains why comfort requirements are different in hot climates, suggesting that more surveys on thermal comfort may be needed in the tropics. In Asia, there has recently been a rapid and widespread diffusion of air conditioners; therefore, a survey was conducted to clarify what temperature and humidity level people in Asian countries prefer in order to feel comfortable. Following that research, this article presents the results of a questionnaire survey on the use of air conditioners in houses in hot, dry climates. Nizwa and Rustak, Oman, characterized by the hot, arid climate of the Arabian Peninsula, were chosen as survey areas. The questionnaire survey was distributed to students of Nizwa University. Questions were asked about the duration of air-conditioner use and preferred air-conditioner temperature settings. To determine how respondents felt about their indoor environment, questions were also asked about the thermal sensations that were experienced while using the air conditioner. In both cities, the mean operating time of the air conditioner was very long. The respondents reported selecting a low temperature setting while sleeping, despite the fact that many of them reported that they were cold while sleeping. Ninety percent of respondents reported a cold, cool, or neutral thermal sensation while using the air conditioner without feeling discomfort.